Analysis of satisfaction of training alumni on types of training at the ambon religious education and training center in 2022 - Edoardus J Ohoiledwarin; Ali Litiloly (Balai Diklat Keagamaan Ambon, 2022)
This study aims to find out about the satisfaction of training alumni with the type of training programmed by the Ambon Religious Education and Training Center. This research method uses quantitative research where the data collection process is in the form of numbers to analyze information about what is to be known, while the method used is the survey method. This type of training is a training service program provided by the Ambon Religious Education and Training Center as a form of public service to stakeholders in its working area. Training is an effort to improve the quality of human resources in accordance with the needs of the job, the type of training provided needs to be evaluated so that it can measure the achievement of service satisfaction and participants' interest in the training program that is carried out. This study concludes that the level of satisfaction of training alumni with regular training is quite good at 47.4%, while the level of satisfaction of training alumni with PDWK training is good at 51.5%, and the level of satisfaction of training alumni with PJJ training is very low, which is 9,91%.